Cardiovascular events associated with thalidomide and prednisone in leprosy type 2 reaction - Alfredo, Melissa de Almeida Corrêa [UNESP]; Schmitt, Juliano Vilaverde [UNESP]; Miola, Anna Carolina [UNESP]; Milagres, Simone de Pádua [UNESP]; Lastoria, Joel Carlos [UNESP] (Elsevier, 2024)
Background: Thalidomide is the drug of choice for the treatment of type 2 leprosy reactions and is often associated with corticosteroids. The use of these drugs in multiple myeloma is associated with the risk of cardiovascular events, but there have been few studies assessing this risk in leprosy patients. Objective: To evaluate the occurrence of cardiovascular events in patients with multibacillary leprosy and their correlation with the use of thalidomide and prednisone. Methods: Analytical cross-sectional study of all patients diagnosed with multibacillary leprosy treated at the Dermatology Service between 2012 and 2022, using electronic medical records. Thromboembolic vascular events, both arterial and venous, including acute myocardial infarction, were considered. The main independent variable was the concomitant use of thalidomide and prednisone during follow-up. Results: A total of 89 patients were included, of which 19 used thalidomide and prednisone concomitantly. There were five cardiovascular events (26.3%), three of which of deep venous thrombosis. The combined use of medications was associated with the events (PR = 6.46 [3.92 to 10.65]; p < 0.01). Study limitations: Small number of events, single-center retrospective study. Conclusion: The hypothesis of an association between cardiovascular events and the concomitant use of thalidomide and prednisone is supported, but more robust prospective studies are required for a better assessment.
Keywords: Leprosy; Thalidomide; Venous thrombosis